The works of Aurelius Augustine: a new translation - Augustine, Saint, Bishop of Hippo. (T. & T. Clark, 1871)
I-II. The city of God, translated by Marcus Dods. [1934]--III. Writings in connection with the Donatist controversy, translated by J.R. King. 1872.--IV. The anti-Pelagian works. v. 1. Translated by Peter Holmes. 1908.--V. Writings in connection with the Manichæan heresy, translated by Richard Stothert. 1872.--VI. Letters. v. 1. Translated by J.G. Cunningham. 1872.--VII. On the Trinity, translated by A.W. Haddan. 1873.--VIII. The Sermon on the Mount expounded, and The harmony of the evangelists, translated respectively by William Findlay and S.D.F. Salmond. 1873.--IX. On Christian doctrine; the Enchiridion; On catechising, and On faith and the Creed. 1892.--X-XI. Lectures or tractates on the Gospel according to St. John. v. 1, translated by John Gibb. 1873; v. 2, by James Innes. [n.d.]--XII. The anti-Pelagian works. v. 2. Translated by Peter Holmes. 1885.--XIII. Letters. v. 2. Translated by J.G. Cunningham. 1875.--XIV. The Confessions, translated and annotated by J.G. Pilkington. [1876?]--XV. The anti-Pelagian works. v. 3. Translated by Peter Holmes and R.E. Wallis. 1876.